2021
DOI: 10.3390/ijerph182211923
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tobacco Use Patterns among Veterans in San Diego during the Recent Peak of the COVID-19 Pandemic

Abstract: The prevalence of tobacco use increases in times of stress; however, during the initial stage of the COVID-19 pandemic, tobacco use rates stayed the same in most populations. Previous work focused on the initial months of the pandemic, while this study examined the changes in tobacco use during a later peak period of the pandemic. We used data from 61,852 visits to the VA San Diego Healthcare System from November 2019 to February 2021, divided into pre-, early, and peak pandemic periods. Multinomial logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
2
2
0
Order By: Relevance
“…Our findings are in line with prior COVID-19 research that showed greater COVID-19 risk perceptions increased motivation to quit and/or promoted reductions in smoking and e-cigarette use [ 20 , 29 , 30 , 31 , 32 , 42 , 43 , 44 , 45 ]. Likewise, the results are consistent with other studies conducted early during the pandemic, which found associations among tobacco use reductions and younger age [ 46 , 47 , 48 ] and Black race [ 31 ]. Beyond replicating the results from recent studies, our study adds to the evidence base on COVID-19 and smoking by characterizing the relation between medical status and smoking changes.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in line with prior COVID-19 research that showed greater COVID-19 risk perceptions increased motivation to quit and/or promoted reductions in smoking and e-cigarette use [ 20 , 29 , 30 , 31 , 32 , 42 , 43 , 44 , 45 ]. Likewise, the results are consistent with other studies conducted early during the pandemic, which found associations among tobacco use reductions and younger age [ 46 , 47 , 48 ] and Black race [ 31 ]. Beyond replicating the results from recent studies, our study adds to the evidence base on COVID-19 and smoking by characterizing the relation between medical status and smoking changes.…”
Section: Discussionsupporting
confidence: 91%
“…Increases in alcohol usage and tobacco as a result of the pandemic have been reported [ 31 ], however, MVP survey respondents primarily reported no increase or not applicable. This is consistent with two survey studies of Veterans which found that alcohol and tobacco use rates stayed the same or declined, at least in the early stages of the pandemic [ 11 , 12 ]. Additionally, items related to smoking and work practices were largely responded to as not applicable, likely given the higher age of respondents.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies found that motivation to quit was strongly associated with the perceived severity of COVID-19, concerns about developing severe illness 24 , 25 , the belief that smokers are at higher risk, stress, and support from close friends and family to quit 22 , 26 . To date, studies have reported that decreases in cigarette smoking were mainly observed among younger age groups 11 , 25 , 27 and smokers with lower levels of nicotine dependence 9 , 10 . In Lebanon, an online survey noted a reduction in smoking after the lockdown among a non-representative sample of 948 young adults 28 .…”
Section: Introductionmentioning
confidence: 99%